Obtaining multifunction additives for middle distillate fuels - Гулямов, Ю.М.; Тертишна, О.В. (Proceedings of National Aviation University (archive), 2006)
The additive for distillate fuels, which allows to improve their operational and technological characteristic. The technology of getting the additive is described. An experimental verification of the additive influence on the main characteristics of the diesel fuel is made.